Quantum Multiagent Actor-Critic Networks for Cooperative Mobile Access in Multi-UAV Systems - Park, Chanyoung; Yun, Won Joon; Kim, Jae Pyoung; Rodrigues, Tiago Koketsu; Park, Soohyun; Jung, Soyi; Kim, Joongheon (IEEE Internet of Things Journal, 2023)
This article proposes a novel algorithm, named quantum multiagent actor-critic networks (QMACN) for autonomously constructing a robust mobile access system employing multiple unmanned aerial vehicles (UAVs). In the context of facilitating collaboration among multiple UAVs, the application of multiagent reinforcement learning (MARL) techniques is regarded as a promising approach. These methods enable UAVs to learn collectively, optimizing their actions within a shared environment, ultimately leading to more efficient cooperative behavior. Furthermore, the principles of quantum computing (QC) are employed in our study to enhance the training process and inference capabilities of the UAVs involved. By leveraging the unique computational advantages of QC, our approach aims to boost the overall effectiveness of the UAV system. However, employing a QC introduces scalability challenges due to the near intermediate-scale quantum (NISQ) limitation associated with qubit usage. The proposed algorithm addresses this issue by implementing a quantum centralized critic, effectively mitigating the constraints imposed by NISQ limitations. Additionally, the advantages of the QMACN with performance improvements in terms of training speed and wireless service quality are verified via various data-intensive evaluations. Furthermore, this article validates that a noise injection scheme can be used for handling environmental uncertainties in order to realize robust mobile access.
Keywords: Aerial base station; Autonomous mobile connectivity system; Decentralised; Decentralized partially observable markov decision process; Mobile connectivity; Non-terrestrial network; Partially observable Markov decision process; Quantum neural networks; Task analysis; Terrestrial networks; Uncertainty; Wireless communications; Aerial base station; autonomous mobile connectivity system; decentralized partially observable Markov decision process (Dec-POMDP); multiagent system; nonterrestrial network (NTN); quantum neural network (QNN)